The Effect of Permeable Pavement Use on Air Temperature of Surrounding Building - Putri Adhitana Paramitha; Ludfi Djakfar; Jyh-Dong Lin; Chen-Yu Hsu (Rekayasa Sipil, 2014)
This paper describe how permeable pavement effects day time and night time thermal environment during summer in subtropical Taiwan. The experiment was carried out on one type of conventional pavement (dense grade asphalt concrete/DGAC) and three types of permeable pavements (permeable asphalt pavement/PAC, concrete, grass block/ GB, and permeable interlocking concrete block/PICB) used 2012 data on summer time (June-September). The result shows that there were surface temperature differencesamong the four types of pavement, particularly during at noon. The use ofpermeable asphalt pavement decreasesthe temperature up to 0.571°C, and up to 10.042°C, and 8.402°C when using GB and PICB, respectively.During the night, there was no difference between DGAC and PAC, while the GB and PICB decreased up to 6.265°C and 5.521°C, respectively.The result also shows that pavement surface temperature affects outdoor and indoor temperature particularly on the 1 st and 2 nd floor.